Functional analysis of the disulphide loop mutant of staphylococcal enterotoxin C2 - Wang, Xiaogang; Xu, Mingkai; Cai, Yongming; Yang, Hongli; Zhang, Huiwen; Zhang, Chenggang (Applied microbiology and biotechnology, 2009)
The superantigen staphylococcal enterotoxin C2 (SEC2) tremendously activate T lymphocytes bearing certain T-cell receptor Vβ domains when binding to MHC II molecules, which launches a powerful response of tumour inhibition in vitro as well as in vivo. However, the toxicity of SEC2 performed in clinic limited its broad application for immunotherapy. The previous studies suggested that the disulphide loop may be important for the toxicity of some SEs, which prompted us to investigate the potential roles of the disulphide loop in biological activity of SEC2. Site-directed mutagenesis was used to disturb the formation of the disulphide bond by substituting Ala or Ser for Cys-93 and Cys-110. The expressed mutants in Escherichia coli were used to determine their superantigen activity and toxicity. Results showed that all of the mutated proteins exhibited reduced abilities to induce T-cell proliferation and cytotoxic effects on tumour cells L929 and Hepa1-6, suggesting that the disulphide loop plays functional role in maintaining the maximal superantigen activity of SEC2. Furthermore, the toxicity assays in vivo showed that all of the mutants induced a reduced emetic and pyrogenic responses compared with native SEC2, which might be important for further construction of lowly toxic superantigen agent.